Alluvial gold dredging: a case study of effects on groundwater turbidity - H. R. Thorpe (The Institute of Materials, Minerals and Mining, 1905)
A floating gold dredge operating in coarse alluvial gravels of the Grey River on the west coast of the South Island, New Zealand, generated high concentrations of clay and colloidal particles in the dredge pond, which entered the groundwater system. Sampling was carried out at depths down to 20 m and it was found that variation of the length of the flow path occurred because of the movement of the dredge towards the piezometers. The alluvial gravels, the suspended sediments, the groundwater system and the water chemistry were all studied. Sediment concentrations were found to be highly variable with depth, but the relative concentrations in the depth profile were generally consistent as the flow distance shortened. The sediments were extremely fine and travelled further through the gravels than predicted. Comparison of field results with the available theory of deep filtration in clean beds of porous media gives some basis for estimating the behaviour of fine sediments in other alluvial systems